A profissão de bombeiro militar sob a ótica da psicodinâmica do trabalho: sofrimento e prazer, riscos e proteção. - Breda, Karine Trarbach de Oliveira (2019)
Military firefighters comprise a professional category that deals with a wide range of activities with varying degrees of complexity, some of which are subject to trauma, post-traumatic stress or even life-threatening. The emergence of the activities and military model of work organization are aspects that integrate this context. Given the above, the present work sought to identify the risks of illness of the profession of military firefighter from Espírito Santo in several aspects, and to verify how these professionals deal with the vicissitudes of work. Two parallel and nonlinear surveys were performed, ie the data from one did not feed the other. The first research sought, through a semi-structured interview, to grasp the perception of Espírito Santo military firefighters about the relationships between their health and their work and to glimpse strategies used by them to deal with the constraints and specificities of the profession. The second research investigated the prevalence of depression, anxiety and stress among military firefighters from Espírito Santo and the relationship of these disorders with aspects related to work organization. The collected data were analyzed with the aid of software and interpreted according to the conceptual theoretical framework of Work Psychodynamics. The results showed that factors related to work organization have a greater influence on the health of the military firefighter from Espirito Santo and that these professionals seek job satisfaction mainly through the positive recognition of the population.